If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.5x + -4.1 = 3.4 Reorder the terms: -4.1 + 2.5x = 3.4 Solving -4.1 + 2.5x = 3.4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4.1' to each side of the equation. -4.1 + 4.1 + 2.5x = 3.4 + 4.1 Combine like terms: -4.1 + 4.1 = 0.0 0.0 + 2.5x = 3.4 + 4.1 2.5x = 3.4 + 4.1 Combine like terms: 3.4 + 4.1 = 7.5 2.5x = 7.5 Divide each side by '2.5'. x = 3 Simplifying x = 3
| 5+2x=53 | | 6(y+4)+5=77 | | 5(2x-6)=6x-7x+14 | | -6(n+4)+27=-3n-12 | | -47+49x=28x+43 | | 7x+5y=102 | | y^2-4y=2x^2 | | x=2y+19 | | 2z+0=x+4 | | 8b-7+8= | | 475-x=x-335+10 | | 3a-b=5b-a | | 100[0.07(y+10)]= | | 450-x=x-335+10 | | 7x+10y=125 | | 5m+8=m | | W+3.75=6.55 | | 2(6x-8)=128 | | 4(2x+7)-3(3x-2)=24 | | 7.73-u=3.73 | | 0.5x+5=19-0.5x | | -(6x-(2x+6))=-3(4(2x-4)-2x) | | 7(4x-9)=-287 | | 770-2x=30 | | x-7-3=-9 | | 3(-1x-1)=-6 | | -(6x-(2x+6))=3-(4(2x-4)-2x) | | 5(-6x+4)=140 | | -(6x-1(2x+6))=3-(4(2x-4)-2x) | | 5(-6x-1)=-335 | | 2(-2+x)=4 | | 3(6+7x)=123 |